Mars and How to Observe It - Grego, Peter; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Mars has long been a favorite subject for astronomers, both amateur and professional. Known as the Red Planet because of its distinct color, it shines brightly in the skies when it is closest to the Earth every two years. Exciting to view through a telescope, this most Earth-like of planets transforms into a real world showing phases, brilliant polar ice caps, seasonal changes in its dusty desert markings, and atmospheric phenomena. Mars and How to Observe It takes readers on a planet-wide tour of the Red Planet and explains how a variety of dynamic forces has shaped it through the ages. This book explains how amateur astronomers can view Mars successfully to create accurate observational drawings and secure high-resolution CCD images of the planet. Peter Grego is an accomplished author, an experienced amateur astronomer who has been actively observing Mars for over 30 years. Using the latest imagery and data from Mars probes and rovers, Mars and How to Observe It presents an up-to-date guide on our current understanding of the Red Planet and how the amateur astronomer can become familiar with this fascinating world.
About the Author -- Introduction -- Section I: Our Current Knowledge of Mars -- Chapter 1: Fourth Rock from the Sun -- Chapter 2: History of the Red Planet -- Chapter 3: Stuff and Substance -- Chapter 4: Atmospherics, Meteors, and Magentic Field -- Chapter 5: The Martian Moons -- Chapter 6: A Topographic Survey of Mars -- Section II: Observing Mars -- Chapter 7: Following Mars -- Chapter 8: A Tour of Mars -- Chapter 9: Recording Mars -- Chapter 10: An Observer's Guide to Martian Apparitions -- Chapter 11: The Mars Observer's Equipment -- Glossary -- Index.
Keywords: Physics; Planetology; Astronomy; Physics; Astronomy, Observations and Techniques; Popular Science in Astronomy; Planetology